Determining radium-226 concentration from radon-222 emanation in building materials: a theoretical model (Brazilian Journal of Radiation Sciences (BJRS), 2019)
It was developed an improved theoretical model capable to estimate the radium concentration in building materials solely measuring the radon-222 concentration in a confined atmosphere.This non-destructive technique is not limited by the size of the samples, and it intrinsically includes back diffusion.The resulting equation provides the exact solution for the concentration of radon-222 as a function of time and distance in one dimension.The effective concentration of radium-226 is a fit parameter of this equation.In order to reduce its complexity, this equation was simplified considering two cases:low diffusion in the building material compared to the air, anda building material initially saturated with radon-222.These simplified versions of the exact one dimension solution were used to fit experimental data.Radon-222 concentration was continuously measured for twelve days with an AlphaGUARD detector, located at the Laboratory of Applied Nuclear Physics at Universidade Tecnologica Federal do Parana (UTFPR).This model was applied to two different materials: cement mortar and concrete, which results were respectively (15.7 +- 8.3) Bq/kg and (10.5 +- 2.4) Bq/kg for the radium-226 effective concentration.This estimation was confronted with the direct measurements of radium in the same materials (same sources) using gamma-ray spectrometry, fulfilled at Centro de Desenvolvimento da Tecnologia Nuclear (CDTN), which results were respectively (13.81 +- 0.23) Bq/kg and (12.61 +- 0.22) Bq/kg.